Gender preference gaps and voting for redistribution - Eva Ranehill; Roberto A. Weber (University of Zurich, Department of Economics, 2021)
There is substantial evidence that women tend to support different policies and political candidates than men. Many studies also document gender differences in a variety of important preference dimensions, such as risk-taking, competition and pro-sociality. However, the degree to which differential voting by men and women is related to these gaps in more basic preferences requires an improved understanding. We conduct an experiment in which individuals in small laboratory "societies" repeatedly vote for redistribution policies and engage in production. We find that women vote for more egalitarian redistribution and that this difference persists with experience and in environments with varying degrees of risk. This gender voting gap is accounted for partly by both gender gaps in preferences and by expectations regarding economic circumstances. However, including both these controls in a regression analysis indicates that the latter is the primary driving force. We also observe policy differences between male- and female-controlled groups, though these are substantially smaller than the mean individual differences - a natural consequence of the aggregation of individual preferences into collective outcomes.
Keywords: C91; C92; J16; H23; 330; Gender differences; risk; altruism; redistributive preferences; experiment; Geschlechtsunterschied; Altruismus; Risikoverhalten; Wahlverhalten; Entscheidungsfindung; Umverteilung; Experiment